Evaluation of peroxide index and oxidative rancidity of broiler diets and the occurrence of breast muscle anomalies - Calasans, Max Weber de Menezes; Furian, Thales Quedi; Borges, Karen Apellanis; dos Santos, Lara Franco; Freitas, Carla Patrícia; Pilotto, Fernando; dos Santos, Luciana Ruschel (Scientia Plena, 2020)
The incidence of breast muscle anomalies, such as white striping (WS) and wooden breast (WB), has increased over the last two decades. These myopathies have different implications on the quality of poultry meat, which depending on the degree of the anomaly, may be rejected due to undesirable appearance or lower technological and nutritional characteristics. Despite the high economic impact, the causes of these myopathies have not yet been defined. The increased susceptibility of poultry to the oxidation process may influence the occurrence of hemorrhagic disorders and muscular dystrophies, necrosis, and fibrosis associated with myopathy with unknown etiology development. Coagulants such as ferric chloride (FC) used in the treatment of effluents can be involved in the feed peroxidation process. Our aim was to evaluate whether the peroxides generated by the presence of FC in poultries’ diets are related to myopathies. Broilers were treated with feed supplemented with 4, 8, or 12 mL FC/Kg of feed. The presence of WS and WB, feed peroxide indices (PI), mean weights, and feed conversion ratios were evaluated. The highest FC concentration indicated higher peroxide production. Addition of 4, 8 and 12 mL of FC yielded 60.0%, 70.0%, and 70.7% of myopathies, respectively, which indicated a possible relationship between food peroxidation and myopathies. Lipoperoxidation resulted in the lowest mean final weight and worsening of the feed conversion in the birds treated with 12 mL of FC. Feed with a high peroxide index is a factor that can increase the incidence of WB and WS.